(untitled) (Biological Sciences - PJSIR, 1998)
Condensation reaction of (IS)-2(a-hydroxy ethyl) benzimidazole (I), 2-hydroxymethyl benzimidazole (II) and 1,2,3 benzotriazole (III) with pyrimidine viz: 2-aminopyrimidine (IV-a) and4, 6-dimethyl-pyrimidine (IV-b) under thecondi- tion of Mannich reaction afforded the hitherto unreported substituted l-arninomethyl (hydroxyalkyl) benzimidazoles and l-aminomethyl benzotriazoles which were assigned the structures (Va-d) and (VIa-b) on the basis of their lR, IH-NMR and HREIMS spectral studies. Antibacterial activity was also evaluated.